The True and False Guide: Characterization in Katherine Govier's Between Men - McCarthy, Dermot (Studies in Canadian Literature)

(untitled) (None, 1996)
Katherine Govier's Between Men is a complex fiction combining elements of the novel of feminist empowerment, historical fiction, contemporary romance, the academic novel, and historiographic metafiction. It develops and weaves -- braids -- three narrative lines together into a composite, intertwined narrative that blurs the boundaries between history and fiction. Govier's use of the "Metafictive Braid" is central to this project of feminist historiography. Analysis of characterization -- particularly the main character in the novel -- reveals its presentation of both false and true guides, as well as its function in driving and determining the plot: a contemporary rewriting of the Orpheus and Eurydice myth, which becomes a story of self-recovery instead of self-loss. Govier's novel is a complex feminist work that closely examines the worlds of public and private history.